Development of an ultra-high vacuum system for space cold atom clock. (June 2015) - Ren, Wei; Xiang, Jingfeng; Zhang, Yuantao; Wang, Bin; Qu, Qiuzhi; Zhao, Jianbo; Ye, Meifeng; Lü, Desheng; Liu, Liang
Abstract: Space cold atom clock (SCAC) is developed for a series of experiments related to laser cooling of atoms and cold atom clock in space microgravity environment. An ultra-high vacuum (UHV) system is the key element for SCAC. This paper presents the design of the UHV system and also shows the status of an initial UHV system prototype with the design and a series of special vacuum treatments whose pressure distribution satisfies the special requirements for SCAC. A dual pumping system, including ion pump and getter, is introduced, and pressures of different positions have been calculated. Experiments have been carried out to acquire the performances of the initial prototype. It is proved that the initial prototype can not only self-sustain an equilibrium pressure for more than 2 months without power but also withstand the mechanical vibration test and space environment simulation test. Furthermore, an optimization design is used to get pressures which are much lower than the desired pressure (∼×10 −8  Pa) in the interaction zone of the system has been demonstrated. Highlights: A UHV system design of the SCAC for space application. A series of special vacuum treatments to reduce the out-gassing and leaking rate. Initial prototype finished mechanical, storage, and maintenance tests for space. System with optimum design can reach a pressure much lower than ∼×10 −8  Pa easily.